2004
DOI: 10.1007/s10591-004-0642-9
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Behavioral Couples Therapy and Emotionally Focused Therapy for Couple Distress

Abstract: Publication information Contemporary Family Therapy, 26 (4): 361-387Publisher Springer Item record/more information http://hdl.handle.net/10197/5128 Publisher's statementThe final publication is available at www.springerlink.comPublisher's version (DOI) http://dx.doi.org/10.1007/s10591-004-0642-9Efficacy of BCT and EFT West Lake Drive, Athens, GA 30606 USA. Nicholsw@aol.com, ABSTRACTEfficacy of BCT and EFT 3 Twenty treatment outcome studies, 13 of which evaluated behavioral couples therapy (BCT) and 7 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
1
8

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 50 publications
2
62
1
8
Order By: Relevance
“…Emotionally-focused Therapy for couples is an empirically-validated approach to treating relationship distress (e.g., Byrne et al 2004;Johnson and Greenberg 1985) with more recent research establishing meta-analytic support for its efficacy (Shadish and Baldwin 2003). The utility of EFT for treating couples with a chronically ill child has been established (Walker et al 1996); importantly, treatment gains from this intervention were sustained or increased at two-year follow up (Cloutier et al 2002).…”
Section: Empirical Support For Eft For Couplesmentioning
confidence: 99%
“…Emotionally-focused Therapy for couples is an empirically-validated approach to treating relationship distress (e.g., Byrne et al 2004;Johnson and Greenberg 1985) with more recent research establishing meta-analytic support for its efficacy (Shadish and Baldwin 2003). The utility of EFT for treating couples with a chronically ill child has been established (Walker et al 1996); importantly, treatment gains from this intervention were sustained or increased at two-year follow up (Cloutier et al 2002).…”
Section: Empirical Support For Eft For Couplesmentioning
confidence: 99%
“…Finally, problem-solving skills are taught to help partners negotiate conflict when it does arise. CBCT has been shown to be effective in the treatment of marital discord: a meta-analysis of seven clinical trials comparing CBCT with waiting-list control groups in treating marital discord yielded a mean effect size (d ) of .95 (Byrne, Carr, & Clark, 2004). This effect size indicates that the post-treatment mean level of marital satisfaction for people who received treatment was nearly one standard deviation higher than the mean level of marital satisfaction for people who did not receive treatment.…”
Section: Cognitive-behavioral Couples Therapymentioning
confidence: 99%
“…Although the target of change in EFT is attachment insecurity, a meta-analysis of seven randomized clinical trials comparing EFT with a waiting-list control group indicated that it also has a positive impact on marital discord, with a mean effect size (d ) of 1.27 (Byrne et al, 2004). This effect size can be interpreted as indicating that the average couple who received EFT was better off at the end of treatment than 89% of untreated couples.…”
Section: Emotion-focused Couples Therapymentioning
confidence: 99%
“…Marital quality and the factors, which affect it, should be considered due to their effect on the psychological health of the couples and children. Experts believe that identification and treatment of harmful factors on the quality of the mutual life can be undeniable on maintaining and promoting the mental health of the couples (Byrne et al, 2004). Nowadays, spouse abuse is one of the main problems of public health with short and long-term consequences on physical and mental health of the couples (Campel, 2002).…”
Section: Introductionmentioning
confidence: 99%